PENGARUH LATIHAN VISUAL DAN PRAKTIK AGILITY LEADER TERHADAP KEMAMPUAN DRIBBLING PADA SISWAUSIA 10-12 TAHUN SSB GANTIMULYO LAMPUNG TIMUR - Bodhiya Braja; Joan Siswoyo; M.Fajril Rifaldo; Surisman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study was to determine the effect of visual training and agility ladder practice on the dribbling ability of students aged 10–12 years at SSB Gantimulyo, East Lampung. This study used an experimental method with a pretest-posttest two-group design. The experimental group received treatment in the form of a visual training program combined with agility ladder practice, which involved agility exercises integrated with visual stimuli to improve players’ coordination and reaction speed while dribbling. The sample consisted of 30 athletes selected using the Ordinal Pairing technique. The results showed that: 1) there was a significant effect of visual training and agility ladder practice on dribbling ability, with the t-test result at a 5% significance level (0.05) showing a t-value of 6.821 greater than the t-table value of 2.160; 2) there was a significant effect of agility ladder practice on dribbling ability, with a t-value of 5.832 greater than the t-table value of 2.160; and 3) there was a significant difference between the visual training and agility ladder practice group and the agility ladder practice group on dribbling ability, with a two-tailed test analysis at a significance level of 0.05 showing a t-value of 2.136 greater than the t-table value of 2.048.